Cardiac Surgery A Commitment to Science, Technology and Creativity - Angel Maluf, Miguel; Roberto Barbosa Evora, Paulo (IntechOpen, 2014)
In this book it is shown how this specialty has evolved over the past 20 years, with significant advances in diagnosis and palliative and definitive techniques for correction of cardiovascular diseases. The book contains 10 cahpters, which are showing the classical adult and pediatric cardiac surgery.